Startup engagement: a strategy framework for established companies (INMR - Innovation & Management Review, 2024)
PurposeEstablished companies often engage with startups as a way to improve their innovation performance. While there has been extensive discussion on the reasons, modes, and expected outcomes of these initiatives, there is still a need to understand more about how corporate engagements with startups (CEwS) evolve and how they can enhance a company’s innovation capability. This study proposes a framework of engagement strategies, discussing their purposes and implications to understand the subject better.Design/methodology/approachThis study involved managers from twelve large, established companies across various sectors. The authors used a multicase approach to analyze their experiences and offer a framework for corporate-startup engagement.FindingsThe framework for corporate-startup engagement consists of four main strategies: (1) innovative improvement, (2) R&D expansion, (3) more value to corporate venture capital and (4) ecosystem articulation. The authors found that ecosystem articulation, which combines the potentials of the other three strategies, is the most sophisticated approach.Originality/valueThis study offers a systematic view of the CEwS phenomenon, identifying the various modes of engagement, the reasons for adopting each one and potential ways to advance and improve them. For managers, the study reveals the CEwS as a lever to build innovation capabilities over time.